Childhood-Onset Systemic Lupus Erythematosus (cSLE): An International Perspective - Aggarwal, Amita; Fernandes, Taciana A. P. [UNESP]; Migowa, Angela; Smith, Eve M. D.; Hanif, Maria; Webb, Kate; Lewandowski, Laura B. (Springer Nature, 2024)
Purpose of Review: Childhood-onset systemic lupus erythematosus (cSLE) is a severe and potentially life-threatening chronic autoimmune disease. cSLE is more aggressive and has poorer outcomes than adult-onset disease. The global burden of cSLE is poorly understood, with most publications on cSLE originating from high-resourced settings. The reports from less resourced settings indicate high morbidity and mortality in these populations. Recent Findings: In this article, we review the disparities in global access to rheumatology care and research for patients with cSLE. We highlight recent cSLE advances from all regions of the globe. We describe current obstacles to cSLE clinical care and research in all settings. Finally, we propose a path forward for high quality, equitable and accessible care to individuals with cSLE everywhere. Summary: Individuals with cSLE are at risk for morbidity and death, yet patients worldwide face challenges to adequate access to care and research. Sustained, collaborative efforts are needed to create pathways to improve care and outcomes for these patients.
Keywords: Childhood-onset lupus; Global health; Lupus; Pediatric; Pediatric rheumatology